Distribution, relative importance and effect of lepidopterous borers on maize yields in the forest zone and midaltitude of Cameroon - Ndemah, R.; Schulthess, F.; Korie, S.; Borgemeister, C.; Cardwell, K.F. (Oxford University Press, 2001)
Geographic distribution, relative importance, and effect of lepidopterous stem and ear borers on maize, Zea mays L., were studied in the humid forest and the mid-altitude zones of Cameroon from 1994 to 1997. Six villages were chosen in the forest zone and grouped into three blocks representing gradients in human population density. A single block with three villages was chosen in the mid-altitude. Farmers’ maize fields were surveyed during the vegetative growth phase for Busseola fusca (Fuller) egg batches, and at harvest for number of larvae and pupae by species, plant damage, and ear weight. There was no significant block effect for any of the variables measured, and most of the overall variance (72–99%) was attributed to within-field variability. In the forest zone, the noctuid B. fusca and the pyralid Eldana saccharina (Walker) accounted for >80% of all species in almost all locations, followed by the pyralid Mussidia nigrivenella (Ragonot) and the tortricid Cryptophlebia leucotreta (Meyrick). The noctuid Sesamia calamistis (Hampson) was found in almost all locations during the first season but disappeared in most locations in the second season. B. fusca egg infestation was significantly higher during the second compared with the first season, whereas larval and pupal densities were much higher during the first season. E. saccharina was the predominant species during the second season, when densities increased fourfold. In the mid-altitude, B. fusca was the predominant species. No significant differences in pest densities, plant damage, and ear weight were found between years. Results of stepwise regression of stem and ear damage on pest densities verified the relative importance of the individual species. In the forest zone, ear and stem damage significantly reduced ear weight, whereas in the mid-altitude only stem tunneling was significant.